2002
DOI: 10.1046/j.1460-9568.2002.02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin protects dopaminergic neurons against lipopolysaccharide‐induced neurotoxicity by inhibiting microglia activation

Abstract: An inflammatory response in the central nervous system mediated by activation of microglia is a key event in the early stages of the development of neurodegenerative diseases. Silymarin is a polyphenolic flavanoid derived from milk thistle that has anti-inflammatory, cytoprotective and anticarcinogenic effects. In this study, we first investigated the neuroprotective effect of silymarin against lipopolysaccharide (LPS)-induced neurotoxicity in mesencephalic mixed neuron-glia cultures. The results showed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
125
0
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 200 publications
(145 citation statements)
references
References 60 publications
12
125
0
8
Order By: Relevance
“…We previously showed that LPS activated p38 and JNK, but not ERK MAPK. The phosphorylation of p38 reached a maximum between 15 and 20 min and JNK remained high for 120 min [15]. These results were consistent with observations that only p38 MAPK inhibitor (SB203580) could inhibit LPSinduced NO production [15].…”
Section: Bt Inhibited Lps-induced P38 Mapk Activationsupporting
confidence: 90%
See 4 more Smart Citations
“…We previously showed that LPS activated p38 and JNK, but not ERK MAPK. The phosphorylation of p38 reached a maximum between 15 and 20 min and JNK remained high for 120 min [15]. These results were consistent with observations that only p38 MAPK inhibitor (SB203580) could inhibit LPSinduced NO production [15].…”
Section: Bt Inhibited Lps-induced P38 Mapk Activationsupporting
confidence: 90%
“…The phosphorylation of p38 reached a maximum between 15 and 20 min and JNK remained high for 120 min [15]. These results were consistent with observations that only p38 MAPK inhibitor (SB203580) could inhibit LPSinduced NO production [15]. Similar to sesame antioxidants [20], BT at a concentration of 50-100 lM, significantly decreased (50-70%) LPSactivated p38 MAPK ( Figure 6).…”
Section: Bt Inhibited Lps-induced P38 Mapk Activationsupporting
confidence: 89%
See 3 more Smart Citations